Avaliação das características tecnológicas de hidromel tipo melomel produzido com diferentes cepas de Saccharomyces cerevisae - Batista, Ana Carolina (2017)
Mead is a fermented drink obtained by diluting honey in water with added nutrients and yeast. In some regions of Europe it is a much consumed and appreciated drink, in Brazil, however, it is little known and exploited. The production of honey is an important activity in Brazil, especially for small producers in the South and Southeast, the development of honey products can be an important alternative for the use of surplus production and as a way of adding value to the product. The work brings as a research the characterization of meads elaborated from different strains of Saccharomyces cerevisiae and added orange juice. The physicochemical analyzes required by the legislation were carried out. Among the three meads produced, only samples 1 resulted in a product within the norms established by the legislation. Samples 2 and 3 presented higher alcohol content, but also higher acidity levels, not so desired in beverage production.